Penilaian Manajemen Risiko K3 menggunakan Metode Severity Index pada Proyek Pembangunan Gedung Laboratorium Terpadu II ITK - Hanun, Fauziah; Situmorang, Raftonado; Fauzi, Ardiansyah; Sari, Oryza Lhara (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
ITK II is an integrated laboratory building construction project currently does not involve identifying hazards, risk assessment, determining risk levels, or comprehensive risk control. The results of observations and interviews by the author show that dangers can arise due to workers' implementation, actions, and unsafe conditions. Based on these conditions, it is necessary to carry out a risk analysis with the aim of knowing what risks may occur, knowing the dominant risk level, and knowing the dominant risk response, as well as providing recommendations for effective risk control on the ITK II Integrated Laboratory Building Construction Project. The approach applied in this research includes a qualitative approach, namely at the survey, observation, interview, and distribution of questionnaire stages, and a quantitative approach is used to assess the probability and impact of risks, sort risks from highest to lowest, categorize risks, and design mitigation. risk.  The severity index method is used to calculate the probability and impact of an event. The calculation is carried out based on responses from respondents using a Likert scale and validated by experts. Then, an analysis of the risk response to the dominant risks is carried out. In the relevance test, the results obtained were 22 relevant variables and 3 irrelevant variables. Furthermore, during the validity test and reliability test, the results of the two tests obtained for each variable were valid and reliable. After that, the risk level was calculated, and 15 dominant sub-risks were obtained with a probability and impact matrix value of 9 in the "high" risk category. Risk responses that can be given are: placing safety signs in the work area, using PPE, increasing signs in each corner of the project, holding short meetings to discuss worker safety aspects regularly before starting work, wearing anti-slip shoes when working in a work environment where there is a risk of slipping, and carrying out regular field supervision.